Probability analysis and reliability evaluation of thermal barrier coating under thermal cycling load using probabilistic statistical method - Lubin Wang; Weize Wang; Jiangling Wan; Junhao Wang; Yangguang Liu (Case Studies in Thermal Engineering)
Thermal barrier coatings (TBCs), commonly used in industrial gas turbines and aero-engines, have become a vital technology for prolonging their lifespan. However, the spalling of TBCs from the substrates during service could compromise the safety and reliability of the equipment. This study presents a methodology for assessing the risk of interfacial spalling induced by thermal stress mismatches between TBCs and their underlying substrates. A life forecasting technique that integrates critical failure probability, probabilistic statistics, and finite element analysis (FEA) was employed in this approach. Initially, FEA was used to establish the relationship between residual stress and thermal cycle. Subsequently, a comprehensive analysis of the failure-related characteristics is conducted to formulate the failure criterion. Then, the probability of failure was computed. The prediction was made for the thermal cycles experienced by the thermal barrier coating (TBC) on disc specimens with varying thermally grown oxide (TGO) thicknesses. The theoretically predicted lifespan was compared to experimental results, indicating the overall life is higher than the predicted value, with a maximum deviation of 16.8 %. Finally, an extensive evaluation was performed to identify the factors that influence the reliability of the TBCs. The investigation revealed that the TGO thickness had the most significant influence on the failure probability of TBCs, while fracture strength is the next important factor. These results have direct guidance for predicting the service life of TBCs and ensuring the service safety of its application components.